2022
DOI: 10.3389/fpubh.2022.1015090
|View full text |Cite
|
Sign up to set email alerts
|

Italian health professionals on the mandatory COVID-19 vaccine: An online cross-sectional survey

Abstract: Italy was the first country in Europe to make vaccination against COVID-19 mandatory for healthcare professionals by imposing restrictions in cases of non-compliance. This study investigates the opinions of the Italian healthcare professionals' categories affected by the regulation. We performed a qualitative online survey: the questionnaire comprised both close- and open-ended questions. The final dataset included n = 4,677 valid responses. Responses to closed-ended questions were analyzed with descriptive st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…About a third of HCWs were in favor of mandatory vaccinations against COVID-19 in a study from Slovenia, while in a study conducted in the Czech Republic, HCWs supported mandatory COVID-19 vaccines for the general population [39,40]. All three included studies from Italy resulted in similar findings, reporting that most of HCWs supported mandatory COVID-19 vaccinations for the general population [41][42][43]. Another four studies (three from the US and one from Barbados) investigated the acceptability of mandatory COVID-19 vaccinations for the general population [44][45][46][47].…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…About a third of HCWs were in favor of mandatory vaccinations against COVID-19 in a study from Slovenia, while in a study conducted in the Czech Republic, HCWs supported mandatory COVID-19 vaccines for the general population [39,40]. All three included studies from Italy resulted in similar findings, reporting that most of HCWs supported mandatory COVID-19 vaccinations for the general population [41][42][43]. Another four studies (three from the US and one from Barbados) investigated the acceptability of mandatory COVID-19 vaccinations for the general population [44][45][46][47].…”
Section: Resultsmentioning
confidence: 89%
“…In 21 of the 30 studies, HCWs placed themselves in favor (>50% acceptance) of mandatory COVID-19 vaccinations for HCWs. With regard to Europe, four studies from Italy were included, which presented a generally supportive stance towards COVID-19 vaccination mandates for HCWs [43,[50][51][52]. All three included studies from Greece consistently showed that HCWs had supportive attitudes towards COVID-19 vaccine mandates for HCWs, unlike the two studies from France, whose authors reported a general trend of opposition [36,[53][54][55][56].…”
Section: Main Findingsmentioning
confidence: 99%
“…Furthermore, Italy was the first country that imposed mandatory vaccinations for its healthcare workers and although 35% of them did not oblige, their reasons revolved around ethical and legal contemplations. 57 However, the benefits and risks of taking a mandatory approach to vaccination, especially the COVID-19 vaccination, are situational and should be weighed against human rights infringements and risk assessments. A study conducted in Cyprus showed that only 27.8% of participants favoured mandatory vaccinations and this increased with age.…”
Section: Discussionmentioning
confidence: 99%
“…Both regions share certain geographical and socioeconomic characteristics, yet they exhibit distinct vaccine uptake patterns [ 11 ]. Comparative data illustrate that South Tyrol’s vaccination rates, apparently influenced by initiatives like the “Green Pass” and mandatory vaccinations [ 48 , 49 , 50 , 51 , 52 ], significantly diverge from those in neighboring Trentino and the national average, reflecting its unique public health landscape. In South Tyrol, the German-speaking [ 13 ], predominantly rural [ 15 ], population tends to exhibit lower rates of acceptance than Italian speakers.…”
Section: Discussionmentioning
confidence: 99%